2005
DOI: 10.1007/s11104-004-0965-1
|View full text |Cite
|
Sign up to set email alerts
|

Root Nitrogen Acquisition and Assimilation

Abstract: Nitrogen (N) is the main mineral element in plant tissues and almost all of this nutrient is acquired from the soil by the roots. Nitrogen is available in many different forms in the soil, but the three most abundant forms are nitrate, ammonium and amino acids. The relative importance of these different soil N pools to a plant is difficult to measure and depends on many different environmental factors. Changes in the available amounts and imbalance in the supply of some N forms can even be toxic to plants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
221
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(232 citation statements)
references
References 305 publications
(292 reference statements)
7
221
0
4
Order By: Relevance
“…Soil amino acid concentrations are also commonly low, relative to [NO 3 − ] and [NH 4 + ], resulting in limited access of plant roots to these N-forms (Jones et al, 2005) and limited potential for fractionation. Nutrient uptake mechanisms allow roots to take up N at low concentrations and consequently deplete soil N to low concentrations (Miller and Cramer 2005), which is consistent with the fact that observed fractionation is especially small when soil [N] are low (Evans 2001;Evans et al 1996;McKee et al 2002;Montoya and McCarthy 1995). It is only when soil [N] is high that significant fractionation may be common.…”
Section: Nitrogen Uptakesupporting
confidence: 82%
See 2 more Smart Citations
“…Soil amino acid concentrations are also commonly low, relative to [NO 3 − ] and [NH 4 + ], resulting in limited access of plant roots to these N-forms (Jones et al, 2005) and limited potential for fractionation. Nutrient uptake mechanisms allow roots to take up N at low concentrations and consequently deplete soil N to low concentrations (Miller and Cramer 2005), which is consistent with the fact that observed fractionation is especially small when soil [N] are low (Evans 2001;Evans et al 1996;McKee et al 2002;Montoya and McCarthy 1995). It is only when soil [N] is high that significant fractionation may be common.…”
Section: Nitrogen Uptakesupporting
confidence: 82%
“…In warmer ecosystems, either NH 4 + or NO 3 − may dominate the inorganic N pool of an ecosystem (Kronzucker et al 1997). Although plants benefit energetically from taking up the most reduced form of N, excessive uptake of NH 4 + can be toxic (Miller and Cramer 2005) and plant N uptake preferences track the availability of different forms of N across different environmental conditions (Wang and Macko 2011). Losses of bioavailable N can be indicative of the N limitation status of plants and microbes and tend to increase with increasing external inputs and availability (e.g., Brookshire et al 2012a;Vitousek et al 1989;Wang et al 2007).…”
Section: Background On the N Cycle And N Isotopesmentioning
confidence: 99%
See 1 more Smart Citation
“…For their different N utilization strategies and aboveground biomass proportions, plants in alpine meadows can be divided into two functional groups, vascular plants and bryophytes. The former is best known as assimilating nutrient primarily from soil with developed root systems (Chapin 1980;vonWiren et al 1997;Miller and Cramer 2005), while the latter is thought to access its major nutrient source from atmospheric deposition due to lack of developed root and vascular systems (Vantooren et al 1990; Ayres et al 2006). Although bryophytes generally appear to rely mainly on atmospheric deposition, the previous research of Polytrichum alpinum and Racomitrium lanuginosum through 15 N tracer applications demonstrated that bryophytes can directly derive N from the soil (Ayres et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The soil ammonium and nitrate concentration ranges from micro molar levels to hundreds of milli molar quantities [1] [30]. The diffusion coefficient of nitrate in soil is the consequence of nitrate available to plant roots and the nitrate lost through leaching (about 30% of inorganic nitrogen) [31] [32].…”
Section: Nitrogen In Soilmentioning
confidence: 99%